The potential of integration: Research progress and key factors of blue-green space perception and health benefits - Xinyi Zhu; Wei Lin; Zhiyi Bao; Chengcheng Zeng; Jian Li; Xiao Qin; Yilun Qu; Wenting Wang; Tianyi Yao (Trees, Forests and People)
With the rapid pace of urbanization, public expectations for the ecological environment have shifted from basic material improvements to more advanced demands for health and well-being. Within the framework of nature-based solutions (NBS), blue-green spaces have emerged as a key factor in enhancing public health. Over the past decade, research on the health benefits of blue-green spaces has grown significantly. This paper examines the research progress and emerging trends in blue-green space perception and its health benefits through a bibliometric analysis of 60 selected articles using Bibliometrix and Microsoft Excel software. The analysis reveals a shift in research focus from isolated perceptions of blue (water) or green (land) spaces to a more integrated understanding of blue-green spaces. The synergistic effects of blue-green integration in promoting health have become increasingly apparent. Consequently, this paper delves into the theoretical foundations of “blue-green space integration” and proposes an “objective-subjective” evaluation framework for integrated blue-green spaces. This framework includes four objective indicators and five subjective indicators. Furthermore, three future research directions are suggested: exploring the mechanisms of blue-green integration's impact on health benefits, expanding a more comprehensive evaluation system for blue-green spaces, and promoting policy support and practical applications for blue-green integration. This study synthesizes the current body of research on blue-green space perception and health benefits, providing guidance for future studies focused on integrated blue-green spaces and contributing to the effective realization of their health-enhancing effects.